The challenges in the development of technological research projects in generational gap contexts - Rodrigues, Rui (2020)
The generational differences that exist in a society or community are not only evidence that one cannot be escape, but a plus for its development. Furthermore, this allows an existence of a connection to the past and as a way of continuity for the future. However, and to increase this importance, the analysis of generational gaps is considered as an aspect that allows development, innovation and creativity, considering the specific context of the research project LOCUS - playfuL cOnneCted rUral territorieS. The article aims to contextualize the generational gaps in Amiais, Sever do Vouga, Portugal and is part of the LOCUS project. The LOCUS project has as main goal to carry out a survey of cultural heritage of the village, with the purpose of developing and apply an Internet of Things (IoT) system for use by residents, stakeholders and visitors. The methodology described in the article is the analysis of the ethnographic research results, namely interviews with privileged informants and informal conversations with residents. Based on these results, it is intended to outline the challenges that are expected to be found in the technological development of the project and the way as it is expected to outcome them.